Flow characteristics of the hydraulic jump in a stilling basin with an abrupt bottom rise; [Caractéristiques du ressaut hydrauliques dans des dissipateurs avec une marche positive et abrupte] - Hager W.H.; Sinniger R.; Karki K.S.; Mishra S.K. (My University, 2025)
The writers comment the authors for their elementary approach to understand the hydraulics of a jump at an abrupt rise of the channel bottom. The writers have also been working on the control of hydraulic jump and drag on baffle piers and wall in it and therefore would like to comment on some basic aspects of forced jump by an abrupt rise. © 1986 Taylor and Francis Group, LLC.